2013
DOI: 10.3182/20130904-4-jp-2042.00071
|View full text |Cite
|
Sign up to set email alerts
|

When is it Fuel Efficient for a Heavy Duty Vehicle to Catch Up With a Platoon?

Abstract: Vehicle platooning has in recent years become an important research field for the vehicle industry. By establishing a platoon of heavy duty vehicles, the fuel consumption can be reduced for the follower vehicles due to the slipstream effect. However, as vehicles are scattered on the road driving by themselves, coordination amongst the vehicles is required. In this paper we study the problem of when it is beneficial for a heavy duty vehicle to drive faster in order to catch up and join a platoon. We derive a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 6 publications
0
47
0
Order By: Relevance
“…The idea of V2V in our paper is similar to the truck platoons [3][4][5]. The difference is that the truck platoon link trucks or cars in train-like line which can save fuel, fit more cars on road, and potentially improve safety.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The idea of V2V in our paper is similar to the truck platoons [3][4][5]. The difference is that the truck platoon link trucks or cars in train-like line which can save fuel, fit more cars on road, and potentially improve safety.…”
Section: Introductionmentioning
confidence: 91%
“…The delay caused by transmission will be lower than 100ms for per frame image. And the effect under 100ms can be ignored in perception systems, which is proved in experiments in [3]. If no objects were detected, vehicle B will stop sending videos and will send stop signal to A, which will terminate the communication between A and B.…”
Section: Dsrc-based V2v Communicationmentioning
confidence: 99%
“…We consider our work to be closely related to [24], which addresses the interesting case of two HDVs that are traveling in the same direction on the same road, but are some distance apart. In this case, it might benefit the trailing HDV to speed up (temporarily using more fuel) in order to catch a leading vehicle and start saving fuel from platooning.…”
Section: Introductionmentioning
confidence: 99%
“…Different works have shown that when multiple vehicles drive within a spatially coordinated scheme such as convoys or platoons, safety can be increased [1], and fuel consumption reduced [2], [3].…”
Section: Introductionmentioning
confidence: 99%